NILAI-NILAI INDIVIDUAL WIRAUSAHA SEBAGAI SUMBERDAYA STRATEGIS DALAM PROSES PEMBENTUKAN KEUNGGULAN KOMPETITIF (Studi Kasus di Unit Usaha Waralaba CV. Inti Sukses Pratama Malang) - Hatneny, Aleria Irma; Saraswati, Ety; Hariri, Hariri; Athia, Ita (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
From the GEM report (Global Entrepreneurship Monitor) small and mediumenterprises can contribute 57% to GDP Indonesia, including entrepreneurship. While thephenomenon is still visible weak competitiveness capabilities in which the data fromGlobal Competitiveness Report 2016-2017 rank Indonesia decreased. The number ofentrepreneurs is also relatively small compared to neighboring countries. From theperspective of entrepreneurship spirit is interesting to examine the values of individualentrepreneurs who have an important role to competitiveness. How the role of individualvalues of entrepreneurs in the process of forming competitive advantage that has highcompetitiveness. From the results of research and discussion obtained the conclusion thatthere are 5 individual values of entrepreneurs are important based on the intensity ofentrepreneurial activity. Individual values are integrated in such a way in corporatestrategy that proved to be an important capital that plays a strategic role for the processof achieving competitive advantage and competitiveness of business organizations.